WHY DO GAMERS PURCHASE VIRTUAL ITEMS IN MOBA GAMES? - Tuzzahra, Andini Ginanti; Edastama, Primasatria (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2023)
This study explores and analyzes multiplayer online battle arena (MOBA) gamers"™ motivation, experience and purchasing behavior in purchasing virtual items. A purposive sampling method was employed and there was a total of 469 respondents participated. The data was analyzed using structural equation modeling-partial least square (SEM-PLS) and partial least square-multigroup analysis (PLS-MGA). The results show that enjoyment, skill, challenge, telepresence, and interactivity have a positive impact on the flow. Further, the flow has a positive impact on both the purchase intention and continuous intention. In addition, both continuous intention and social value have a positive impact on the purchase intention. Lastly, the shopping enjoyment strengthens the positive impact of flow on both the continuous intention and purchase intention; and the positive impact of continuous intention on the purchase intention is strengthened by both shopping enjoyment and age. These findings highlight that there are many factors influencing the purchase intention of MOBA games"™ virtual items, and provide a valuable contribution to practitioners and academics in relation to the factors influencing the MOBA gamers"™ purchase of virtual items.JEL: M31.